Late results of oesophageal and oesophagogastric resection in the treatment of oesophageal cancer. Issue 1 (January 1971) - Ward, A. S.; Collis, J. Leigh
Abstract : Oesophageal resection with oesophagogastric anastomosis is said to be followed by severe oesophagitis. Little is known, however, of the late results of this technique in patients with oesophageal carcinoma and the present communication records our experience with 23 long-term survivors. Except for one patient with recurrent carcinoma, all were in good health and taking a normal diet. Loss of weight, which is a normal sequel to oesophagogastric resection, was prevented by inserting two extra meals a day. Anaemia was not a problem and there was no evidence of vitamin B12 or folate deficiency. None of the patients had any symptoms of oesophagitis, though all exhibited free reflux on recumbency. After operation patients are advised to sleep propped up and to avoid stooping or lying flat. These measures are thought to be largely responsible for the absence of oesophagitis in our series. Five patients were achlorhydric and 10 hypochlorhydric in response to intravenous pentagastrin (6 μg/kg per hour). Mean basal output was 0·6 mEq/hour and mean maximal output 8·8 mEq/hour.